Engineering of bulk and fiber-shaped YAGG:Ce scintillator crystals. Issue 6 (24th January 2017) - Sidletskiy, O.; Gerasymov, Ia.; Kurtsev, D.; Kononets, V.; Pedash, V.; Zelenskaya, O.; Tarasov, V.; Gektin, A.; Grinyov, B.; Lebbou, K.; Auffray, E.; Dormenev, V.; et al.
Abstract : Fast and bright Y3 Al5− x Ga x O12 :Ce, Ca garnet scintillation crystals were developed for high energy physics detectors. Abstract : Composition-property correlations have been systematically studied in the full concentration range of Y3 Al5− x Ga x O12 :Ce (YAGG:Ce) scintillator crystals. The most promising compositions for new high energy physics experiments at colliders have been determined with the light output >200% relative to BGO and fast luminescence decay. Codoping with Ca 2+ provides the decrease of phosphorescence intensity to 0.2% after 0.6 μs and shortening of the luminescence decay constant to 21 ns. Factors affecting the scintillation decay time in YAGG:Ce have been discussed. The crystals show weak transmission loss under γ-irradiation. The feasibility to produce YAGG:Ce fibers using the μ-PD method has been shown.